Pengaruh Social Media Marketing, Electronic Word of Mouth, Dan Kualitas Pelayanan Terhadap Keputusan Pembelian Konsumen Terhadap Dashoescare Denpasar - Putri, Sukmasari Triana Gita; Narayan, I Nyoman Gede Gita (Training & Research Institute - Jeramba Ilmu Sukses, 2025)
The study aims to examine and analyse the impact of social media marketing (SMM), electronic word-of-mouth (eWOM), and service quality on purchasing decisions. This research was conducted at Dashoescare, located in Denpasar, involving 76 respondents selected using the Slovin formula. All data were collected through questionnaires and were declared valid for use. They were analysed using multiple linear regression and hypothesis testing (t-test and F-test). This study reveals that: (1) Social media marketing, electronic word of mouth, and service quality have a positive influence on purchasing decisions at Dashoescare, Denpasar. (2) Social media marketing has a positive impact on purchasing decisions at Dashoescare, indicating that improvements in social media marketing can increase purchasing decisions. (3) Electronic word of mouth also contributes positively to purchasing decisions, explaining that the more effective this strategy is, the greater the purchasing decisions by consumers. (4) Service quality shows a positive influence on purchasing decisions, explaining that improvements in service quality can encourage better purchasing decisions at Dashoescare.